Barbecue : The History of an American Institution, Revised and Expanded Second Edition - Moss, Robert F., 1970- (Book collections on Project MUSE., 2020)
"A revised and expanded second edition of the definitive history of an iconic American food, barbecue, from its historical origins to the present"--